(untitled) (Research, Society and Development, 2024)
Anabolic androgenic steroids (AAS) have been widely used to improve physical performance and modify body appearance, driven by increasing social pressure for idealized aesthetic standards. Studies indicate that the use of AAS, especially nandrolone, is associated with a variety of adverse effects, including cardiovascular and neuropsychiatric complications, and cellular damage with carcinogenic potential. This study aims to evaluate the carcinogenic effects of nandrolone, one of the most common anabolic steroids. Through a narrative review of quantitative studies, the risks involved in the abusive use of this substance were analyzed, with emphasis on the development of cancer. The results suggest that high doses of nandrolone can cause genetic damage, in addition to promoting oxidative stress in several tissues, which plays a significant role in the formation of tumors. Therefore, prolonged and indiscriminate use of nandrolone is a relevant risk factor for health, especially with regard to the development of neoplasias.